The Lesson Observation for the Productive Learning Environment in English Classes: Stories from Two Elementary Schools - Bunga Ayu Wulandari; Syahrial Syahrial; Andari Amalia Syahrial; Yundi Fitrah (Indonesian Research Journal in Education |IRJE|, 2022)
In Indonesia, English is not required for the elementary school students in the current curriculum. This  qualitative case study examines the role of teachers in providing a productive learning environment through classroom activities in English classes at two elementary schools in Jambi, a province in Indonesia.. The productive learning environment is characterised by target-oriented, genuine and real-based learning, encouraging and appealing activities, dynamic and accommodating knowledge formation, autonomous, and contemplative. The data were gathered from observations in 7 classes and teacher interviews. This research revealed that there was not a single meeting that altogether covered the six features of a productive learning environment. Therefore, it is suggested that teachers should understand more about a productive learning environment to empower classroom activities to help students achieve educational goals.